Nanotechnology-based Solutions for Beta-thalassemia: Unravelling Curcumin as a Promising Therapeutic Agent - Rahul. E (Medical Science: Recent Advances and Applications Vol. 4, 2025)
Background: Beta thalassemia is a blood disorder that affects the production of hemoglobin, the protein responsible for transporting oxygen throughout the body. It is caused by a mutation in the gene that controls the production of hemoglobin beta globin chains. Beta thalassemia is a group of inherited blood disorders characterised by decreased Hb production, which leads to anaemia, and the body does not have healthy RBCs. Individuals need regular blood transfusions. Thus, transfusions frequently result in side effects, including iron toxicity. A polyphenol called curcumin has anti-inflammatory effects and can raise the body’s level of antioxidants. The use of nanocurcumin has shown a better treatment option for beta-thalassemia conditions. Objective: To evaluate the better treatment option for beta thalassemia using nano curcumin as a therapeutic tool. Methods: A comprehensive search to identify the relevant studies was conducted in online databases, mainly Google Scholar, PubMed, Embase, and Scopus. Around 100 articles were identified, and after the title and abstract review, 23 students were included in the review. A literature search was conducted to gather information on beta-thalassemia, nanotechnology, and curcumin. Peer-reviewed articles, scientific journals, and relevant databases were utilised to identify relevant studies and research findings. The search was focused on studies that investigated the application of nanotechnology in beta-thalassemia management and the potential benefits of curcumin in this context. Results: Nanotechnology offers promising strategies for beta-thalassemia management, enhancing drug delivery and gene therapy. Curcumin, with its antioxidant and anti-inflammatory properties, is being explored for beta-thalassemia but faces bioavailability challenges. Strategies like nanoformulations are being investigated for curcumin’s delivery. Conclusion: Nanotechnology-based diagnostics, including non-sensory and nano-biosensors, hold promise for early detection and monitoring of beta-thalassemia. Curcumin mitigate oxidative stress, reduce inflammation, and potentially alleviate the damage to beta-thalamic RBCs. However, the bioavailability of curcumin remains a challenge, and strategies to enhance its delivery and stability need to be investigated.